LEXICAL-SEMANTIC CHARACTERISTICS OF LAPART GENRE REFERENCE UNITS IN KHORAZM FOLKLORE (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article discusses the lapar genre typical of Khorezm folklore. It is about the lexical-semantic features of the units of reference found in the composition of the words.